La máquina óptica : Lo humano como imagen - Prósperi, Germán Osvaldo (2017)
The aim of this chapter is to return to the category of "anthropological machine" developed by Furio Jesi and Giorgio Agamben considering it, as suggested by the latter, in terms of an "optical machine", an artifact constituted by two eyes and two looks: the eye of the soul and the eye of the body. Our objective is to explain the main aspects of this historical artifact that produces images of the human.